Look behind you eaudiobook - Johansen, Iris (Kendra Michaels, 2017)
A serial killer is on the loose in San Diego, and he has a most unusual M.O.: With each kill, he leaves behind objects with unclear meanings. Most of the recent killings are centered near Kendra Michaels' home and office, so it comes as no great surprise when the FBI shows up at her door. The investigators soon make a startling discovery: the left-behind objects are actually souvenirs of other unsolved serial murder cases in various U.S. cities. And the new cases feature "holdback" characteristics of the other murders unknown to the general public. Kendra realizes that the killer has come to challenge and taunt her. The investigators become his newest targets, even as Kendra slowly begins to suspect that one of them may be the killer himself. She must find the killer as the body count rises, and to do so she relies on her own "dream team" of agent-for-hire Adam Lynch and private investigator Jessie Mercado. They must risk everything to defeat a psychopath whose terrifying plan is years in the making.